Exogenous glycine betaine alleviates dynamic physiological and transcriptomic responses in Inula salsoloides under combined salt-cadmium stress - Wang, Heyi; Wang, Lei; Zhang, Xiaomin; Cao, Lu; Wang, Guiquan; Zhang, Yunpeng; Hao, Quan; Re, Ze; A, Ruhan; Zhe, Zhicheng; Yan, Xiaoyun (Frontiers in Plant Science, 2026)
IntroductionInula salsoloides, a psammophytic and salt-tolerant xerophyte is ecologically valuable for windbreaks, sand fixation, and the restoration of saline-alkali lands. However, the regulatory mechanisms through which exogenous glycine betaine (GB) alleviates combined salt-cadmium stress in this species remain unclear.MethodsThis study investigated the protective effects of foliar-applied GB on Inula salsoloides seedlings under individual salt, cadmium, and combined salt-cadmium stress through a systematic analysis of seed germination, seedling growth, key physiological and biochemical parameters, and transcriptome sequencing.ResultsThe salt, cadmium, and combined salt-cadmium stress significantly suppressed seed germination and seedling growth, impaired photosynthetic pigment synthesis, and induced oxidative damage, as reflected by reactive oxygen species accumulation and membrane lipid peroxidation. Exogenous GB application effectively mitigated these adverse effects, increasing germination potential, vigor index, and biomass. Physiologically, GB promoted the accumulation of osmoprotectants and enhanced antioxidant enzyme activities, thereby restoring cellular osmotic and redox homeostasis. Transcriptomic analysis revealed that GB reprogrammed the expression of genes enriched in key metabolic pathways, including carbon fixation in photosynthetic organisms, glyoxylate and dicarboxylate metabolism, and particularly, arginine and proline metabolism under combined stress. GB also modulated the expression of numerous stress-related transcription factors.DiscussionOur findings demonstrate that exogenous GB enhances the tolerance of Inula salsoloides to salt and cadmium stress by coordinating physiological and transcriptional responses. This study provides novel insights into the mechanisms of GB-mediated stress alleviation and supports its potential application in enhancing plant ecological resilience in saline and heavy metal-contaminated environments.